Hypertrophic Cardiomyopathy - Čapek, P.; Škvor, J. (Methods of Information in Medicine, 2006)
Objectives: Our research is a pilot study that specializes in the molecular genetic investigation of the TNNT2 gene in Czech patients with HCM/FHC disease. This study was initiated with exons 9 and 11 of TNNT2 because of their crucial role in the binding ability of cardiac troponin T to α-tropomyosin, and continued with analyses in other regions of the gene.Methods: Hundred and eighty-one Czech probands with HCM/FHC were enrolled in this study. The study group consisted of 24 families with FHC and probands without FHC history but with HCM diagnosis. The clinical diagnosis was based on echocardiography. DNA was isolated from peripheral blood lymphocytes and subsequently analyzed by the polymerase chain reaction (PCR), followed by DNA sequencing analyses, which were cross-sequenced.Results: The ΔGlu160 mutation was observed in a sequence of the TNNT2 gene in a patient with the severe form of hypertrophic cardiomyopathy. No sequence alteration was found in exons 9 and 11 of the TNNT2 gene found in the rest of the DNA samples.Conclusion: The ΔGlu160 mutation was observed in patients with severe forms of hypertrophic cardiomyopathy. This region is responsible for binding troponin T to α-tropomyosin. This mutation may lead to functional and structural effects on the troponin T protein. Mutations in this region are reported relatively rarely and therefore it was unique to observe the ΔGlu160 mutation in our study.
Keywords: Cardiomyopathy; hypertrophic; familial; TNNT2 gene; mutation